The Involvement of miRNA in Carotid-Related Stroke. Issue 9 (September 2017) - Maitrias, Pierre; Metzinger-Le Meuth, Valérie; Nader, Joseph; Reix, Thierry; Caus, Thierry; Metzinger, Laurent
Abstract : Cardiovascular disease is the leading cause of morbidity and mortality in developed countries. Stroke is associated with a marked disability burden and has a major economic impact; this is especially true for carotid artery stroke. Major advances in primary and secondary prevention during the last few decades have helped to tackle this public health problem. However, better knowledge of the physiopathology of stroke and its underlying genetic mechanisms is needed to improve diagnosis and therapy. miRNAs are an important, recently identified class of post-transcriptional regulators of gene expression and are known to be involved in cerebrovascular disease. These endogenous, small, noncoding RNAs may have applications as noninvasive biomarkers and therapeutic tools in practice. Here, we review the involvement of several miRNAs in cell-based and whole-animal models of stroke, with a focus on human miRNA profiling studies of carotid artery stroke. Lastly, we describe the miRNAs' potential role as a biomarker of stroke.